2010
DOI: 10.1007/s00216-010-3604-0
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative screening of phenolic compounds in olive leaf extracts by hyphenated liquid chromatography and preliminary evaluation of cytotoxic activity against human breast cancer cells

Abstract: In this work, high-performance liquid chromatography (HPLC) coupled to electrospray time-of-flight mass spectrometry (ESI-TOF-MS) and electrospray ion trap multiple-stage tandem mass spectrometry (ESI-IT-MS(2)) has been applied to screen phenolic compounds in olive leaf extracts. The use of a small particle size C18 column (1.8 micro) provided great resolution and made separation of a lot of isomers possible. The structural characterization was based on accurate mass data obtained by ESI-TOF-MS, and the nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
134
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(154 citation statements)
references
References 38 publications
20
134
0
Order By: Relevance
“…The later-eluting peak was identified as the isomeric secologanoside, which elutes after oleoside under reverse-phase conditions. 14 The MS of the peaks arising at 30.6 min (Peak O5) and 34.6 min (Peak O8) displayed a precursor ion at m/z 555; the MS 2 spectrum obtained by fragmentation of this ion presented the following m/z values: 537, 393, and 323, described in literature for 10-hydroxy oleuropein and maybe one of its isomers.…”
Section: Lc-ms Analysismentioning
confidence: 82%
See 1 more Smart Citation
“…The later-eluting peak was identified as the isomeric secologanoside, which elutes after oleoside under reverse-phase conditions. 14 The MS of the peaks arising at 30.6 min (Peak O5) and 34.6 min (Peak O8) displayed a precursor ion at m/z 555; the MS 2 spectrum obtained by fragmentation of this ion presented the following m/z values: 537, 393, and 323, described in literature for 10-hydroxy oleuropein and maybe one of its isomers.…”
Section: Lc-ms Analysismentioning
confidence: 82%
“…For the remaining compounds for which no standards were available, identification was based on accurate mass measurements of the pseudomolecular [M-H] -ions and their fragmentation pattern as documented in the literature. 13,14 The total ion current (TIC) chromatograms of MOLE and AOLE are presented in Figure 1. Data obtained from the ESI-MS n analysis of the extracts are summarized in Table 1.…”
Section: Lc-ms Analysismentioning
confidence: 99%
“…Several studies have shown that olive leaf extract exhibits a large spectrum of in vitro and in vivo properties, including antioxidant activity [85,86], radio-protective effects [85], anti-proliferative effect on leukemia cells by inducing apoptosis [39,57,87,88], cytotoxic activity against human breast cancer cells [47,89], anti-HIV virus effect [90], antifungal activity [91], gastroprotective activities [92], attenuation of diabetic neuropathic pain [93] and amelioration of gentamicin nephrotoxicity [94]. Several biological properties such as antioxidant, anti-atherosclerotic, hypoglycemic and cardioprotective effects of olive leaves have been reviewed in the literature [76,82].…”
Section: Benefits Of Olive Leavesmentioning
confidence: 99%
“…Hydroxytyrosol and tyrosol are described as the main representatives of the simple phenolic compounds in olive leaves and in olives [12,[40][41][42][43][44][45][46][47][48].…”
Section: Polyphenolic Compounds In Olive Leavesmentioning
confidence: 99%
“…Based on these findings, increasing research interest has been focused on the deeper understanding of the mechanisms of action of these compounds. For these purposes, however, wide-scope flavonoid profiling methods are required that can provide comprehensive information regarding the various forms of flavonoid compounds in the sample [6][7][8].…”
Section: Introductionmentioning
confidence: 99%